Hydrogenation of Alpha-pinene over Nickel Nanoparticles under Mild Condition Pressure - Rizqi Alima Fabri, Ahmad; Warsito, Warsito; Ulfa, Siti Mariyah; Masruri (Chemistry Department, The University of Brawijaya, 2024)
Alpha-pinene is the main compound in turpentine oil and is widely used as a fragrance, fine chemistry, flavour, and antibacterial. Due to the presence of unsaturated double bonds in its structure, this compoundâ€™s chemical properties are relatively active. Hydrogenation is a common method for saturating compounds and nickel has shown good activity in this process as catalysts. However, it often shows reaction conditions such as high pressure. The research method added nickel chloride to a suspension mixture of NaBH4 in isopropyl alcohol until a black colloidal solution and a-pinene reagents were added. Hydrogen gas was added in different conditions, with a pressure of 2-4 atm at the temperature of 50-60 oC 24h. The result showed a nickel formed at a nanoparticle size of 34-81 nm. Furthermore, FT-IR results show a difference in intensity at wavelengths of 1600 and 3000 cm-1, indicating the formation of hydrogenation products. The GC-MS shows a new peak at a retentivity of 5.503, which characteristics show that it is identified as a pinane compound with the highest percentage of 63% at a reaction condition of 4 atm.Â